The role of institutions in shaping the internationalization process: A case study of private and state Chinese firms - JING, TONG (2017)
Over the past few decades, internationalization has become critical for the global competitiveness of Chinese firms. Firms internationalize with different drivers and undergo different processes. This study examines the internationalization process of state-owned and privately-owned Chinese companies and how institutions alter this process. The study builds on case studies of two smart phone companies – Huawei and ZTE in order to provide new insights about the internationalization strategy and driving forces of firms from emerging markets. Specifically, this research examines and explores two key questions that are both theoretically and practically important. First, whether and how firms from emerging markets follow the Uppsala model in the course of their internationalization and how these firms differ from their counterparts from developed markets in this regard. Second, whether and how institutions twist the internationalization path of state-owned and privately-owned firms from the Uppsala model differently. The analysis is framed from the institution-based view in the light of governments, ownership structures and CEO’s personal experience. By analyzing the case studies of Huawei and ZTE, it is suggested that the internationalization path of Huawei is more likely to abide by the Uppsala model, whilst the internationalization process of ZTE is not consistent with the theory of the Uppsala model because of the role of institutions. However, it is the close relationship with the government that makes internationalization seen as a threat to the host countries’ security. With research discussions and findings, this dissertation aims to enhance our understanding of the impacts of the Uppsala model and institutions on the internationalization path of emerging market enterprises (EMEs), and furthermore to realize that not all firms will evolve their internationalization following the Uppsala model.